SLOBODAN TIŠMA, AN ARTIST IN FIRST PERSON (Philological Studies, 2019)
The work is conceived as an example of reading the literature that arises as a romanticized documentation of the “invisible art practice”(an art that is aligned with life). The art of the Novi Sad Circle (Vladimir Kopicl, Slobodan Tišma, Miroslav Mandić, Božidar Mandić, Vojislav Despotov, Judita Šalgo, Mirko Radojičić and others) is an example of the reliance of conceptual and "poor" art practices (arte povera) on the documentary power of literature. The strangeness of this literature is not contained solely in its ability to conserve "invisible" artistic practices. What is its characteristic is a new type of storyteller and heroes: an artist in first person – artist who’s performing in front of the reader.In this case, theartistain first personis Slobodan Tišma.
Keywords: Invisible art, performance, romanticized documentation, autography, artist in prima persona